Transcriptional profiling of immune responses in NHPs after low-dose, VSV-based vaccination against Marburg virus - Cecilia A. Prator; Brianna M. Dorratt; Kyle L. O’Donnell; Justin Lack; Amanda N. Pinski; Stacy Ricklefs; Craig A. Martens; Ilhem Messaoudi; Andrea Marzi (Emerging Microbes and Infections)
Infection with Marburg virus (MARV), the causative agent of Marburg virus disease (MVD), results in haemorrhagic disease and high case fatality rates (>40%) in humans. Despite its public health relevance, there are no licensed vaccines or therapeutics to prevent or treat MVD. A vesicular stomatitis virus (VSV)-based vaccine expressing the MARV glycoprotein (VSV-MARV) is currently in clinical development. Previously, a single 10 million PFU dose of VSV-MARV administered 1–5 weeks before lethal MARV challenge conferred uniform protection in nonhuman primates (NHPs), demonstrating fast-acting potential. Additionally, our group recently demonstrated that even a low dose VSV-MARV (1000 PFU) protected NHPs when given 7 days before MARV challenge. In this study, we longitudinally profiled the transcriptional responses of NHPs vaccinated with this low dose of VSV-MARV either 14 or 7 days before lethal MARV challenge. NHPs vaccinated 14 days before challenge presented with transcriptional changes consistent with an antiviral response before challenge. Limited gene expression changes were observed in the group vaccinated 7 days before challenge. After challenge, genes related to lymphocyte-mediated immunity were only observed in the group vaccinated 14 days before challenge, indicating that the length of time between vaccination and challenge influenced gene expression. Our results indicate that a low dose VSV-MARV elicits distinct immune responses that correlate with protection against MVD. A low dose of VSV-MARV should be evaluated in clinical rails as it may be an option to deliver beneficial public health outcomes to more people in the event of future outbreaks.